O vídeo no jornalismo convergente e móvel: um estudo de mídias independentes brasileiras - Barros, Leandra Eloy Ribeiro (2019)
Independent journalism, from Brazilian media that was born in a contemporary context, inaugurates new formats of building and spreading the news, through a convergent and mobile work in networks, which also uses videos in its narratives in an innovative way. This mobile and convergent journalism, with the use of new technologies, reinvents the way to produce audiovisual, called for some Post-TV. This study aims to analyze the use of videos by seven important independent media in the Brazilian scenario - Congress in Focus, Studio Fluxo, Jota, Ninja Media, Nexo Jornal, Reporter Brasil and The Intercept Brasil -, understanding the production of video and its uses in narratives. presented. For such, we take as theoretical reference the studies of journalism and its productive processes of Traquina and Wolf, besides the theorists of mobile journalism and media convergence, such as Jenkins, Salaverría and Avilés. The exploratory qualitative methodology consists of a survey and bibliographic study. And, in the field research, in-depth interviews with journalists who are leaders in these vehicles, as well as a content analysis of selected videos of these media, since the interest in studying them arises mainly from the new narratives and formats. produced by many of them.